Shift From Face to Face Classes to Distance Learning: Best Practices of Selected Private Secondary Schools in the Municipality of Daraga and City of Legazpi - Lopo, Arjie (JPAIR Multidisciplinary Research, 2025)
This study investigates the shift from face-to-face classes to distance learning in response to frequent class suspensions impacting students’ education in the Philippines. It aims to identify the strategies employed by selected private secondary schools in the Municipality of Daraga and City of Legazpi, assess the effectiveness of these approaches, evaluate the key factors contributing to successful implementation, and develop a comprehensive manual for distance learning procedures. Utilizing a quantitative research design, data were collected through survey questionnaires distributed among principals, teachers, and senior high school students from ten participating schools for the academic year 2024-2025. The findings revealed that a variety of strategies were adopted to maintain educational continuity, with effective communication, parental involvement, and community collaboration highlighted as crucial for success. Additionally, challenges related to resources and access were noted, indicating a need for ongoing support. The study concludes that while schools demonstrated adaptability in their transition to distance learning, continuous evaluation and improvement of distance education practices are essential to ensure equitable access and positive learning outcomes for all students. The proposed Manual of Operation aims to guide future efforts in this area, emphasizing the importance of robust leadership and stakeholder engagement.